Overlooked anterior anal misplacement: a 'forme fruste' anomaly and potentially correctable cause of constipation - Amr Abdelhamid AbouZeid; Amr Abdel Rahman AbdelMalek; Omar Goda Hassan; Shaimaa Abdelsattar Mohammad (SpringerOpen, 2024)
Abstract Purpose To share our experience in the management of a specific type of mild anorectal anomaly presenting with severe constipation. Methods Data of patients with idiopathic constipation who were referred to our pediatric surgical facility during the period from 2013 to 2023 were retrospectively analyzed. The study included patients with significant symptoms of constipation associated with a minor degree of unrecognized anterior anal misplacement. MRI was ordered in most cases to confirm the presence of deeper structural abnormalities. Results Data from 16 cases were available for retrospective analysis. All included cases underwent posterior anoplasty with posterior sphincterotomy. Postoperative recovery was uneventful in all cases with no wound complications. Almost all cases reported obvious improvement of symptoms regarding frequency of defecation and relief of straining which was the most distressing preoperative complaint. After 1 month, 12 cases were off laxatives with regular defecation; 3 cases still required lower doses of laxatives. Only one case reported unsatisfactory response up to 3 months postoperatively, and unfortunately was lost to follow-up. Five cases responded to messages sent to them through registered phone numbers and were available for longer-term follow-up. Conclusion Mild unrecognized forms of anorectal anomalies may present with idiopathic constipation. Severe straining at defecation is an important clue. The subtle abnormality on perineal examination can be supported by pelvic MRI unveiling more structural abnormalities at a deeper level. Posterior anoplasty offered relief of symptoms in most cases.